Life Skill Education Through Extracurricular Religion In The Tunadagsa Children In SLBN Gending - Moh. Rifa’i; Ely Sunariya (International Journal of Education, Information Technology, and Others, 2020)
This study aims to determine the life skill education of children with physical disabilities through religious extracurricular activities at SLBN Gending, Probolinggo, East Java. The research design used is descriptive qualitative research in the form of data exposure in the field of study under study. Data collection techniques used are direct observation, interviews, and documentation. The data analysis model used was using the Miles and Huberman technique, namely data reduction, data exposure / presentation, and conclusion drawing. The results of the research obtained were that there were several religious extracurricular activities at SLBN Gending, including praying together before and after carrying out learning activities, praying Duha and Zuhur in congregation, memorizing prayers and short letters, reciting the Koran, and studying have a good character. Children with physical disabilities will acquire four skills, namely personal skills (the ability to know themselves and their God), academic skills (the ability to think intelligently according to religious demands), social skills (the ability to have a social character with religious values ​​that have been embedded in them), and vocational skills (The ability to have potential skills and vocational skills about religion